Cambio Climático: Ventana de Oportunidad para las Fuerzas Armadas en las estrategias de adaptación y mitigación - Miranda Alfaro, Víctor Arturo (2022)
This article exposes and analyzes different actions in which the Armed Forces can participate taking advantage of what Kingdon (1984) calls «windows of opportunity», which will remain open for short periods and if they are not taken advantage of in the political process, the opportunity cost will be lost, and it will be necessary to wait for another one to appear again at a certain moment; all this with the purpose of strengthening the State’s capacity to benefit the population and of having a country on the path to sustainable development. The Armed Forces play a very important role in the State’s sustainability strategy, and they have managed to be considered as an insurance against future conflict scenarios related to climate change. They could participate in supporting society through a significant contribution to adaptation to climate change. In this sense, the armed forces should be strategically considered and prepared as a risk manager.